Lactic acid-based fermentative hydrogen production from kitchen waste: Mechanisms and taxonomic insights - Luo, Lijun; Lim, Roktaek; Pradhan, Nirakar (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•Optimal lactic acid-based H2 production was observed at a pH range of 5.5 to 6.•Lactobacillus was the dominant lactate-producing genera for kitchen waste fermentation.•H2 production was achieved by decomposition of lactate through clostridial-type fermentation.•pH levels >6 adversely affected H2 production and increased propionate accumulation.•A two-phase Gompertz model accurately adjusts the successive stages of H2 production. Lactic acid production under anaerobic dark fermentation is inversely related to hydrogen (H2) production. In this study, a novel pH regulation mechanism was proposed to convert lactic acid to H2. The study also investigates the roles played by dominant microbial communities and enzymes in the degradation of kitchen waste, resulting in lactic acid accumulation and its subsequent conversion to H2. Furthermore, a two-phase Gompertz function was applied to describe the cumulative H2 production, with the first phase representing H2 production from readily degradable sugars, followed by the second phase representing H2 production from lactic acid conversion. The study finds that the optimal H2 production from lactic acid occurred within a pH range of 5.5 to 6.0. When the pH exceeded 6.0, it led to propionic acid accumulation and a subsequent reduction in H2 production. The observed H2 yield was found to be 39.23 ± 2.29 mL-H2/g of volatile solids (VS) for the pH-unregulated experiments and 28.60 ± 2.78 mL-H2/g VS for the pH-regulated experiments. Finally, microbial community analysis reveals that Lactobacillus (relative abundance (RA): 63–66 %) and Bifidobacterium (RA: 19–21 %) are the dominant lactate producers in the initial phase, while Megasphaera (RA: 26 %), Veillonella (RA: 3.4 %), and Clostridium sensu stricto 7 (RA: 5 %) are the primary lactate utilizers and H2 producers in the subsequent phase. These findings highlight the mechanistic understanding of lactic acid-based H2 production from putrescible organic waste like kitchen waste and enhance the understanding of the acidogenic phase of anaerobic digestion.